Trace Amine-Associated Receptors as Novel Therapeutic Targets for Immunomodulatory Disorders - Christian, Sherri L.; Berry, Mark D. (Frontiers in Pharmacology, 2018)
Trace amines and their receptors (trace amine-associated receptors; TAARs) are an emerging pharmacological target for the treatment of human disorders. While most studies have focused on their therapeutic potential for neurologic and psychiatric disorders, TAARs are also expressed throughout the periphery, including prominent expression in human leukocytes. Furthermore, recent independent, unbiased metabolomic studies have consistently identified one or more TAAR ligands as potential etiologic factors in inflammatory bowel disease (IBD). The putative role of TAARs in diseases such as IBD that are associated with hyperactive immune responses has not, however, previously been systematically addressed. Here we review the current state of the knowledge of the effects of TAARs on leukocyte function, in particular in the context of mucosal epithelial cells that interface with the environment, developing a model whereby TAARs may be considered as a novel therapeutic target for disorders associated with dysregulated immune responses to environmental factors. In this model we hypothesize that altered trace amine homeostasis results in hyperactivity of the immune system. Such loss of homeostasis can occur through many different mechanisms including TAAR polymorphisms and altered trace amine load due to changes in host synthesis and/or degradative enzymes, diet, or dysbiosis. The resulting alterations in TAAR functioning can then lead to a loss of homeostasis of leukocyte chemotaxis, differentiation, and activation, as well as an altered ability of members of the microbiota to adhere to and penetrate the epithelial cell layers. Such changes would generate a pro-inflammatory state at mucosal epithelial barrier layers that can manifest as clinical symptomatology such as that seen in IBD. These alterations may also have the potential to induce systemic effects, which could possibly contribute to immunomodulatory disorders in other systems, including neurological diseases.